2019
DOI: 10.1002/eji.201948156
|View full text |Cite
|
Sign up to set email alerts
|

Biologicals targeting type 2 immunity: Lessons learned from asthma, chronic urticaria and atopic dermatitis

Abstract: During the last decades, progression of research has led to great achievements for treatment and therapy of several disabling disorders, particularly in the field of chronic inflammatory diseases. The increased knowledge of the molecular mechanisms operating in such diseases has represented the first step in this process, and the discovery of molecules able to interfere with the natural history of the diseases, has been the second. This review is focused on the effects of biologics on type 2 diseases such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Preclinical studies have clearly shown that ILC2s promoted Th2-cell differentiation since, in their absence, Th2 response in mice is impaired when challenged with allergens or parasitic worms [15,54]. Accordingly, in humans, an increased number of ILC2s and activity were observed in patients with Th2-oriented disorders as respiratory allergy, atopic dermatitis, chronic rhinosinusitis and eosinophilic esophagitis [45,[54][55][56][57][58][59][60]. Notably, intrahepatic ILC2s contribute also to the process of fibrogenesis in liver diseases through secretion of AREG [61].…”
Section: Enhancing and Regulatory Function Of Ilc2smentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical studies have clearly shown that ILC2s promoted Th2-cell differentiation since, in their absence, Th2 response in mice is impaired when challenged with allergens or parasitic worms [15,54]. Accordingly, in humans, an increased number of ILC2s and activity were observed in patients with Th2-oriented disorders as respiratory allergy, atopic dermatitis, chronic rhinosinusitis and eosinophilic esophagitis [45,[54][55][56][57][58][59][60]. Notably, intrahepatic ILC2s contribute also to the process of fibrogenesis in liver diseases through secretion of AREG [61].…”
Section: Enhancing and Regulatory Function Of Ilc2smentioning
confidence: 99%
“…Indeed, it has been shown that ILC2s may exert APC activity for naïve CD4+ T cells since they express MHC-Class II and costimulatory molecule OX40L [45,58,64]. IL-4 has also trophic activity on basophils and mast cells (MC) which are short-lived circulating cells recruited to inflammatory sites (basophils) or long-lived tissue resident cells (MC) [45,47,55,59].…”
Section: Enhancing and Regulatory Function Of Ilc2smentioning
confidence: 99%
See 1 more Smart Citation
“…This approach aims at the active induction of neutralizing autoantibodies against effector cytokines in allergic diseases. The active immunization approach follows a similar logic as passive immunization with biologics, which, in the recent years, has become an established treatment for severe cases of, e.g., allergic asthma by targeting effector molecules critically involved in the allergen‐specific immune response like IL‐4, IL‐5, or IL‐13 . However, compared to the high treatment costs and efforts (repeated injections) associated with passive immunization, active immunization against immune effector molecules might be advantageous, because it could represent a more cost‐effective therapy with the potential to induce a durable, long‐term, and polyclonal response against the targeted molecules.…”
Section: Vnp‐based Strategies For Allergy Treatmentmentioning
confidence: 99%
“…The latest GINA recommendations suggest the use of mepolizumab as an add-on treatment for patients with severe eosinophilic asthma [2]. Mepolizumab is an IgG1/k class-humanized monoclonal antibody which blocks circulating interleukin-5 (IL-5) which is responsible for the development, maturation, and survival of eosinophils [3]. Several randomized controlled trials have shown the efficacy and safety of mepolizumab in patients with severe eosinophilic asthma [4][5][6]; however, to date, only a few studies have shown its effectiveness in a real-life setting [7][8][9].…”
Section: Introductionmentioning
confidence: 99%